The impact of war on ACS admissions and triage – a single center experience - Sharon Bruoha; Tatiana Stolichny; Vladimir Chitoroga; Michael Shilo; Michael Friger; Jamal Jafari; Evgeny Chernogoz; Maggie Cohen Grisaru; Amos Katz; Chaim Yosefy; Gili Givaty (Heliyon)
Introduction: Contemporary data regarding the impact of war on cardiovascular disease is scarce. The Israel-Gaza war that erupted on October 7th, 2023, provided a tragic opportunity to explore the effect of war on the epidemiology, characteristics, and management of patients with acute coronary syndrome (ACS) living in areas of active armed conflict. Methods: All patients admitted with ACS to our medical center, between October 7th, 2023, and January 6th, 2024, were retrospectively included. Crucial time intervals in the management of individuals with ACS were collected in a predetermined spreadsheet. In-hospital and 30-day outcomes were obtained from the medical records and contrasted with ACS cases admitted in the period preceding the war. Results: A total of 449 individuals (102 females [22.7 %]) with a diagnosis of ACS were recruited, 358 patients (144 STEMI and 214 NSTEMI) were admitted during the 9 months before October 7th and 91 patients (42 STEMI and 49 NSTEMI) in the 3 months after October 7th. Compared to the control period, a significant reduction in ACS admissions per month was noted (38.91 vs. 28.79, p < 0.001) driven by fewer cases of both STEMI and NSTEMI (15.65 vs. 13.29, p = 0.011 and 23.26 vs. 15.5, p < 0.001, respectively). In patients with STEMI, the total ischemic time was similar before and after the war (179 min vs. 187 min, p = 0.849). Conclusions: War has a dramatic impact on cardiovascular incidence and outcomes which, however, are not necessarily linked to higher admission rates. Nevertheless, with the adoption of systematic approach and increased awareness, patients with ACS can be managed effectively even at times of extremely limited resources such as war.